Cerebral Hemodynamic Evaluation After Cerebral Recanalization Therapy for Acute Ischemic Stroke - Zhang, Zhe; Pu, Yuehua; Mi, Donghua; Liu, Liping (Frontiers in Neurology, 2019)
Cerebral recanalization therapy, either intravenous thrombolysis or mechanical thrombectomy, improves the outcomes in patients with acute ischemic stroke by restoring the cerebral perfusion of the ischemic penumbra. Cerebral hemodynamic evaluation after recanalization therapy, can help identify patients with high risks of reperfusion-associated complications. Among the various hemodynamic modalities, magnetic resonance imaging, computed tomography perfusion, and transcranial Doppler sonography are the most commonly used. Poststroke hypoperfusion is associated with infarct expansion, while hyperperfusion, which once was considered the hallmark of successful recanalization, is associated with hemorrhagic transformation. Either the hypo- or the hyperperfusion may result in poor clinical outcomes. Individual blood pressure target based on cerebral hemodynamic evaluation was crucial to improve the prognosis. This review summarizes literature on cerebral hemodynamic evaluation and management after recanalization therapy to guide clinical decision making.